IRONIC AND NOSTALGIC PICTURE OF THE 60’ IN PÉTER TÍMÁR’S FILM DOLLYBIRDS (CSINBABA, 1997) - Bubak, Grzegorz (Porównania, 2013)
Péter Tímár’s film Dollybirds (Csinibaba, 1997) discovered uncharted territory and made the Hungarians realize that perhaps even subconsciously, they feel nostalgia for the sixties. After the revolution of 1956, year by year the Hungarians started to believe that it is possibile to live in that system, you just have to find the right place for yourself and lay low. Tímár decided to use those memories combined with popular music tracks in his film, in an adaptation of Gyula Márton’s short story.